Clinical effeciency of mineral waters in complex treatment of non-alcohol fatal disease liver - I. B. Zabolotna (Kazimierz Wielki University, 2018)
The article presents an experimental substantiation of the efficiency of the use of boric carbon dioxide hydrocarbonate sodium mineral water of average mineralization in rats with a model of non-alcoholic fatty liver disease. As a result of the experimental research, improvement of the morphological picture of the liver under the influence of the course drinking of mineral water has been proved. During clinical studies there was an improvement in the clinical course of the disease, the restoration of the functional state of the liver, a decrease in signs of dyslipidemia and insulin resistance, and a decrease in the level of leptin.